PENERAPAN MEDIA PEMBELAJARAN TIMELINE BERBASIS CANVA UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN SEJARAH KELAS XI SMA NEGERI 4 LUBUK LINGGAU - Riska Dui, Richi; Wulan Sari, Ratna; Sofiarini, Andriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the implementation of Canva-based timeline learning media in improving students' learning interest in History learning at the eleventh grade of SMA Negeri 4 Lubuklinggau. This study employed a quantitative approach using a One-Shot Case Study design. The sample consisted of 36 students from class XI.4 selected through purposive sampling. Data were collected using a learning interest questionnaire that had been validated by experts. The data were analyzed using descriptive statistics, normality testing, and hypothesis testing with the assistance of IBM SPSS Statistics 24. The results showed that the average percentage of students' learning interest reached 85.28%, which was categorized as very high. The hypothesis test showed a significance value of 0.000 (<0.05); therefore, H₀ was rejected and Hₐ was accepted. Thus, the implementation of Canva-based timeline learning media had a positive effect on improving students' learning interest in History learning.